Chapter Dante e la Slovacchia: traduzione, ricezione e studi danteschi dopo il 1989 - Šavelová, Monika (Biblioteca di Studi di Filologia Moderna, 2022)
The aim of the paper is to outline the main developments in research, translation and reception of Dante's work in Slovakia after 1989. The period in question is particularly significant for the overall evaluation of the translation and reception of Dante's work from the 19th century and for the basis of the comparative translation and literary research of the last decade, including new translations.